Quantum Computing as a Global Game Changer in Technological Transformation towards National Resilience - Edi Permadi; Margaretha Hanita; Stanislaus Riyanta; Ahmad Ibrahim Badry (Jurnal Lemhannas RI, 2025)
Purpose: This study investigates the implications of quantum computing for Indonesia’s national resilience by placing digital security, data sovereignty, and governance preparedness as the focus of analysis. It examines how quantum technology may affect the stability and adaptive capacity of Indonesia’s national resilience system, particularly in the dimensions of cybersecurity, defence, and strategic governance. Study Design/Methodology/Approach: This study uses a descriptive qualitative approach based on an analysis of international and domestic literature published between 2018 and 2025, using Indonesia’s national resilience framework, including Asta Gatra and ATHG, combined with Complex Adaptive Systems theory to examine the interactions of actors, institutions, and technologies in facing strategic disruption in the quantum computing era. Findings: The findings reveal that the US, China, Japan and the EU have created advanced and coordinated quantum research ecosystems. quantum computing presents risks to public-key cryptography, digital infrastructure, signals intelligence, data sovereignty, and several dimensions of Asta Gatra because of limited human resources, insufficient research facilities, fragmented regulation, and the absence of an integrated post-quantum cryptography roadmap. This risk advocates for immediate actions such as the creation of a post-quantum cryptography roadmap, cryptographic asset mapping across public institutions, and national coordination in digital security. Long-term responses should include strengthening technological sovereignty, developing advanced quantum education, and building national research capacity in post-quantum security. Originality/Value: This study presents a new insight by incorporating quantum computing into Indonesia’s national resilience analysis through the Asta Gatra, ATHG, and Complex Adaptive Systems frameworks and gives policy recommendations for Indonesia to increase its technological sovereignty and adaptive capacity at an early stage in the quantum revolution.